2013
DOI: 10.1111/tri.12174
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin-mediated protection in kidney transplantation: nonerythropoietic EPO derivatives improve function without increasing risk of cardiovascular events

Abstract: SummaryThe protective, nonerythropoietic effects of erythropoietin (EPO) have become evident in preclinical models in renal ischaemia/reperfusion injury and kidney transplantation. However, four recently published clinical trials using high-dose EPO treatment following renal transplantation did not reveal any protective effect for short-term renal function and even reported an increased risk of thrombosis. This review focusses on the current status of protective pathways mediated by EPO, the safety concerns us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…,31 and by the gradual expansion of peritoneal effusion.HIF-1α is an important pathway of IRI [32][33][34]. EPO upregulation is important for hypoxia adaptation,35 improving renal function and structure in rats 36. EPO upregulation is important for hypoxia adaptation,35 improving renal function and structure in rats 36.…”
mentioning
confidence: 99%
“…,31 and by the gradual expansion of peritoneal effusion.HIF-1α is an important pathway of IRI [32][33][34]. EPO upregulation is important for hypoxia adaptation,35 improving renal function and structure in rats 36. EPO upregulation is important for hypoxia adaptation,35 improving renal function and structure in rats 36.…”
mentioning
confidence: 99%
“…GATA4 and GATA5 regulate BCL2L1 gene expression against cardiotoxic agents and hypoxic stimuli, respectively (Aries, Paradis, Lefebvre, Schwartz, & Nemer, 2004;Wu, Wang, Lin, Liu, & Chen, 2016). In addition to these broad observations of the relationship between cellular responses to stressors and GATA factors, EPO exerts critical cytoprotective functions, and this notion is supported by various observations (Joyeux-Faure, 2007;Maiese, Li, & Chong, 2005;Mammis, McIntosh, & Maniker, 2009;van Rijt, van Goor, Ploeg, & Leuvenink, 2014;Sharples & Yaqoob, 2006). Therefore, we suggested that GATA factors may act to tune and optimize the local levels of EPO production through binding to the GATA-binding motif Genes to Cells KANEKO Et Al. in the promoter-proximal region.…”
Section: Discussionmentioning
confidence: 69%
“…Cardiovascular risk associated with EPO treatment may be reduced by using other EPO derivatives. [2728] We observed that in vitro stimulation of rat whole blood with high concentration of rHuEPO did not alter any agonist-induced aggregation. Therefore it seems feasible that rHuEPOdoes not exert direct effects on circulating platelets, but rather modulates platelet during synthesis and maturation in the bone marrow.…”
Section: Discussionmentioning
confidence: 91%